Mining exceptional Rasch models - Kiefer, Ch; Sengewald, M. A. (Behaviormetrika, 2025)
The detection of differential item function (DIF) is a crucial task in item response theory modeling. In recent years, machine learning (ML) techniques are increasingly used for this task, for example, using model-based recursive partitioning (MOB) techniques. For example, Rasch trees are a combination of MOB and Rasch models. In this paper, we propose an alternative ML technique for DIF detection in Rasch models, called exceptional model mining in Rasch models (RaschEMM). While Rasch trees and RaschEMM share an algorithmic base and the goal to identify covariate-based subgroups, they have different goals. Rasch trees aim at identifying a “global model of the data”, whereas RaschEMM aims at identifying exceptional subgroups. After a general and comprehensive presentation of RaschEMM, we present the results from two simulation studies and provide an applied example.
CRIS-Team Scopus Importer:2025-09-22
Keywords: Differential item functioning; Machine learning; Rasch model; Subgroup discovery